(untitled) (Journal of Parents and Teachers, 2024)
Generative Artificial Intelligence has become a topic of discussion and debate in all social and professional fields and education has not been left behind. We need to have the necessary pause for reflection and enough audacity to take advantage of it so that we are able to first understand and then use all the possibilities it offers us in pursuit of a more just and equitable educational and societal model. In this article we will see some whys and some hows in relation to the potential of AI in the field of Academic and Professional Guidance.